A chat with Dr. Birama Sidibe, Founder of Agrobiotech, Mali (Episode 2) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In this episode, Dr Sidibe talks about how innovation has helped make a difference in what they do at Agribiotech